Analisis Pelayanan Tiket Terhadap Kepuasan Penumpang KM. Sinabung pada PT. Pelayaran Nasional Indonesia Cabang Surabaya - Yuliana; Poli, Sofyan (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
PT. PELNI is a company engaged in the field of marine transportation services ie passenger ships. The importance of "service" to the satisfaction of passengers is very influential, Services passenger can be defined as any form of services passengers and in-kind, which in principle is the responsibility and implemented by government institutions at the central, local, and in the state-owned enterprises, or enterprises in an effort to meet the needs of society as well as in the framework of the provisions of the legislation. This research was conducted in order to determine the performance of services and determine the level of satisfaction of service users Services to PT. PELNI. The study design used is descriptive qualitative. The results of this study are as follows. First, from the aspect of quality of service to passengers PT. PELNI employee attitudes and, generally unsatisfactory service performance, but still need some improvements in order to provide maximum service to all service users by the PT. PELNI. Second, based on passenger feedback to the facilities provided by the PT. PELNI still lack a place where ticket sales and ticket counter, causing long queues of passengers who pose a mutual struggle to quickly get into the KM. Sinabung. Third to the security of the passengers were still causing unrest and losses on the passenger against the persistence of the brokering or counterfeit tickets, clashes between passengers. This means that most of the passengers wanting to improve on three indicators and should be a priority in improving the service by the parties in the future PT. PELNI provide services.